Toxoplasma gondii in dromedary camels (Camelus dromedarius) in Egypt: a comparative seroepidemiological study in Upper and Lower Egypt - Ehab Kotb Elmahallawy; Ehab Kotb Elmahallawy; Nady Khairy Elbarbary; David Cano-Terriza; David Cano-Terriza; Tomás Fajardo; Nada Oudah Albalawi; Débora Jiménez-Martín; Marwa M. I. Ghallab; Ahmed Gareh; Refaat Ras; Refaat Ras; et al. (Frontiers in Veterinary Science)
Toxoplasmosis remains a prevalent parasitic zoonosis worldwide, raising public health concerns. The global information available regarding the role of camels in the epidemiology of Toxoplasma gondii is still limited. This study aimed to assess the seroprevalence of T. gondii in dromedary camels (Camelus dromedarius) from northern and southern Egypt. A total of 513 serum samples were obtained from camels across Cairo (Lower Egypt) and Aswan (Upper Egypt) governorates. The Modified Agglutination Test (MAT) was performed to screen for anti-T. gondii antibodies. The overall seroprevalence was 13.84% (71/513; 95CI%:10.85–16.83). The bivariate analysis showed that animals aged 4–8 years (13.84%, 36/260) and older than 8 years (18.45%, 31/168) showed significantly higher seropositivity compared to those young individuals (≤ 4 years old) (p = 0.011). Additionally, the multiple logistic regression analysis highlighted the geographic region as a potential risk factor for T. gondii exposure. Thus, camels from Lower Egypt had significantly higher seroprevalence of T. gondii (19.92%, 51/256) compared to those from Upper Egypt (7.78%; 20/257; p < 0.001; odds ratio [OR] = 2.94; 95% CI: 1.70–5.10). Our results provide evidence of moderate, widespread, and heterogeneous spatial distribution of T. gondii among camel populations in Egypt, which might have important implications for animal and public health in that country. Surveillance and control programs should be implemented to reduce the risk of exposure of T. gondii in camels.